Peningkatan Menulis Puisi berdasarkan Peristiwa yang Pernah Dialami pada Siswa Kelas VIII SMP Negeri 4 Kotabumi, Lampung Utara - Riska Alfiawati; Rohana Rohana; Sri Wahyuningsih (LPPM STKIP PGRI Bandar Lampung, 2025)
The issue raised in this study is the improvement of students' ability to write poetry. This study was conducted with the aim of identifying and describing the level of ability and weaknesses in writing poetry using appropriate word choice, rhymes, figures of speech/imagery, and imagery. The data in this study is useful as information for teachers, especially Indonesian language teachers. In an effort to improve the results of poetry writing learning and to achieve the objectives of the research conducted at SMP Negeri 4 Kotabumi Lampung Utara, a quantitative descriptive method was used. The population in this study consisted of 151 students in class VIII B, comprising 68 male students and 64 female students spread across four classes, namely VIII A, VIII B, VIII C, and VIII D. A sample of 30 students was taken from the population of 151 students, selected randomly using the stratified proportional random sampling technique. The technique used for data collection was a performance test, in which students were assigned to write their own poems based on events they had experienced, taking into account the requirements for writing poetry. Based on the results of the data analysis, it was concluded that the poetry writing skills of eighth-grade students at SMP Negeri 4 Kotabumi Lampung Utara were categorized as “fair.”